2009
DOI: 10.1369/jhc.2009.952739
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activity and Immunohistochemical Localization of Dipeptidyl Peptidase 8 and 9 in Male Reproductive Tissues

Abstract: (XC) S U M M A R Y The mRNA expression pattern of dipeptidyl peptidase (DPP) 8 and DPP9, two DPP4 homologs, was studied previously and showed a broad tissue distribution. In this study, protein expression and activity of DPP8 and DPP9 were investigated in male reproductive tissues of different mammals. Based on specific DPP activities and inhibition profiles, the proline-selective DPP activity in the bovine and rat testis could predominantly be attributed to DPP8/9 and not to DPP4. This is in contrast to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
5
25
0
1
Order By: Relevance
“…The predominant reason for carcinogenesis can be attributed to the down‐regulation of tumor suppressor genes and the up‐regulation of oncogenes or cancer‐promoting genes 20. The DPP4 enzyme family is expressed and is found in all normal human adult and neonatal tissues 21, 22, 23…”
Section: Discussionmentioning
confidence: 99%
“…The predominant reason for carcinogenesis can be attributed to the down‐regulation of tumor suppressor genes and the up‐regulation of oncogenes or cancer‐promoting genes 20. The DPP4 enzyme family is expressed and is found in all normal human adult and neonatal tissues 21, 22, 23…”
Section: Discussionmentioning
confidence: 99%
“…19 It is worthwhile to stipulate that DPP9 potencies reported can reasonably be expected to also be indicative for inhibitor affinities toward the highly homologous DPP8. 26,27 The results summarized in Table 2 show that the N-(4-quinolinoyl) substituted compound 7 has about 60 times more FAP-affinity than the initial N-(1-naphthoyl) based 'hit' 3. Its potency as an inhibitor of FAP also clearly stands out among the other compounds in Table 2.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…As the increased transcription of genes in the MSYq deletion mice is thought to lead to a corresponding increase in their encoded proteins, we decided to examine the expression of the EGFP transgene at the protein level. Western blot analysis demonstrated that GFP levels are increased by more than twofold in the 2/3MSYq-testes compared to XY controls using both a whole testis (actin) or spermatid-specific (DPP9) (Dubois et al, 2009) protein as a loading control (Fig. 2A,B and supplementary material Fig.…”
Section: Testis Protein Levels Of Upregulated Sex-linked Genes Are Inmentioning
confidence: 99%